Morphology control of extruded polystyrene foams with benzene-trisamide-based nucleating agents. (May 2019) - Aksit, M; Klose, B; Zhao, C; Kreger, K; Schmidt, H-W; Altstädt, V
Polystyrene is a low-priced, amorphous polymer, showing excellent foaming behavior. Polystyrene foams are widely used in a variety of applications including insulation panels for building and construction. In this context, foam morphology plays a significant role to tune the macroscopic properties of the foams and research focusses on the fabrication of foams with homogenous morphology and an average cell size distinctly below 100 µm at densities lower than 100 kg/m³. Here, we demonstrate how 1, 3, 5-benzene-trisamides can be used as supramolecular foam nucleating agents to control the morphology of extruded amorphous polystyrene foams. Depending on the concentration and the processing temperature, benzene-trisamides can be homogeneously dissolved in the polystyrene melt. Upon cooling, the benzene-trisamides self-assemble into finely dispersed, solid supramolecular nano-objects, which subsequently act as nucleating sites for foam cell formation. Various concentrations of the benzene-trisamide-based additive were selected to systematically study the influence of the morphology of the extruded polystyrene foams. In the same way, neat polystyrene foams were produced as a reference. We found that for extruded polystyrene foams with 0.2 wt% of additive, the cell sizes were significantly reduced by a factor of 35 from 632 to 18 µm compared to those of a neat extruded polystyrene reference foam.